Depressive symptoms among poor older adults in Mexico: prevalence and associated factors Síntomas depresivos en adultos mayores pobres de México: prevalencia y factores asociados - Ietza Bojorquez-Chapela (Revista Panamericana de Salud Pública, 2009)
OBJECTIVE: To describe the presence of depressive symptoms (DS) and factors associated with them among poor Mexican older male and female adults (OA). METHODS: A survey was conducted among OA enrolled in a governmental poverty relief program (Oportunidades) in Mexico. Participants completed a short version of the Center for Epidemiologic Studies Depression Scale and answered questions about health and life conditions. RESULTS: The prevalence of DS over the cutoff point was 43% (confidence interval (CI) 39.5-46.4). DS were associated with different variables among male and female participants. For men, difficulties in performing daily life activities were associated with DS over the cutoff point (odds ratio (OR) 2.62, CI 1.58-4.34) and literacy was associated with less DS (OR 0.46, CI 0.31-0.68). For women, difficulties with daily life activities were associated with more DS (OR 2.50, CI 1.57-3.97), and being head of the family was also positively associated (OR 1.81, CI 1.11-2.93). CONCLUSIONS: DS were frequent among this sample of poor OA. The differences between men and women in variables associated with DS highlight the importance of considering the gendered aspects of growing old. OBJETIVO: Describir la presencia de síntomas depresivos (SD) y los factores asociados con ellos en adultos y adultas mayores pobres de México. MÉTODOS: Se realizó una encuesta a adultos y adultas mayores registrados en un programa gubernamental de alivio de la pobreza (Oportunidades) en México. Los participantes completaron una versión abreviada de la Escala de Depresión del Centro de Estudios Epidemiológicos y respondieron preguntas sobre su salud y condiciones de vida. RESULTADOS: La prevalencia de SD por encima del nivel de corte fue de 43% (intervalo de confianza de 95% [IC95%]: 39,5 a 46,4). Los SD se asociaron con diversas variables en los hombres y mujeres participantes. En hombres, la dificultad para realizar actividades de la vida diaria se asoció con la presencia de SD por encima del nivel de corte (razón de posibilidades [odds ratio, OR] = 2,62; IC95%: 1,58 a 4,34) y saber leer se asoció con menos SD (OR = 0,46; IC95%: 0,31 a 0,68). En las mujeres, la dificultad para realizar actividades de la vida diaria se asoció con más SD (OR = 2,50; IC95%: 1,57 a 3,97), al igual que ser la cabeza de la familia (OR = 1,81; IC95%: 1,11 a 2,93). CONCLUSIONES: Los SD fueron frecuentes en esta muestra de adultos mayores pobres. Las diferencias entre hombres y mujeres en cuanto a las variables asociadas con los SD subrayan la importancia de tomar en cuenta los aspectos de género asociados con el envejecimiento.